Separación y divorcio en México : una perspectiva demográfica - Ojeda de la Peña, Norma (El Colegio de México A.C., 1986)
This paper seeks to analyze the stability of conjugal unions in Mexico over time and their relationship to certain sociodemographic factors. The information contained in the Mexican Fertility Survey of 1976, with regard to the following aspects, was used: the type or nature of the union at the time of its inception; the age of the woman at the time of her first union; the existence or lack of premarital fecundity; the educational level of the woman; work experience or lack thereof prior to the union; and the rural/urban situation underlying the process of socialization of the woman. Among the most important findings of the research are that first- time, urban unions are more likely to end in divorce or separation than rural or semi-urban ones. Similarly, a real increase in the probabilities of dissolution over time was observed, which led the author to suggest that a weakening in the conjugal link in the youngest unions is beginning to be observed in Mexico.